Estimating Potential Growth in the Middle East and Central Asia - Mitra, Pritha (IMF Working Papers; Working Paper ;, 2015)
The Middle East and Central Asia's economic growth potential is slowing faster than in other emerging and developing regions, dampening hopes for reducing persistent unemployment and improving the region's generally low living standards. Why? And is it possible to alter this course? This paper addresses these questions by estimating potential growth, examining its supply-side drivers, and assessing which of them could be most effective in raising potential growth. The analysis reveals that the region's potential growth is expected to slow by 3/4 of a percentage point more than the EMDC average over the next five years. The reasons behind this slowdown differ across the region. Lower productivity growth drives the slowdown in the Caucasus and Central Asia and is also weighing on growth across the Middle East (MENAP); while a lower labor contribution to potential growth is the main driver in MENAP. Moving forward, given some natural constraints on labor, total factor productivity growth is key to unlocking the region's higher growth potential. For oil importers, raising physical capital accumulation through greater investment will also play an important role.